A novel cholesterol-free mayonnaise made from Pickering emulsion stabilized by apple pomace particles. (15th August 2021) - Lu, Zhiqiang; Zhou, Siyuan; Ye, Fayin; Zhou, Gaojuan; Gao, Ruiping; Qin, Dingkui; Zhao, Guohua
Highlights: Pickering emulsion stabilized by apple pomace is used as cholesterol-free mayonnaise. A new opportunity for the utilization of by-products of food industry. NMs exhibit acceptable appearance and rheological properties compared to CM. NMs show super stability under 210-day storage (25 °C) without oil–water separation. Abstract: Yolk-based mayonnaise is widely used to enhance the flavor of daily food. In view of health concerns on dietary cholesterol, novel mayonnaises (NMs) were made from Pickering emulsions stabilized by apple pomace particles using micro-jet (MJ-NM), ultrasonic (US-NM), and high-speed-shear homogenizer (HSS-NM), respectively. NMs and commercial mayonnaise (CM) were comparatively investigated in appearance, droplet size, rheological, tribological, and stability properties. NMs presented almost identical appearances to CM except for color. The droplets' size in NMs were larger than CM. Both NMs and CM demonstrated shear-thinning behavior and solid-like properties. Among mayonnaises, MJ-NM was demonstrated the most rapid thixotropy recovery with its storage modulus recovered within 51 s. Although both NMs and CM were of mixed tribology nature, NMs presented lower oral lubricity. Upon 210-day storage, both NMs and CM exhibited excellent stabilities without any oil–water separation occurred. Overall, the Pickering emulsions are promising and health alternatives for traditional mayonnaise.